PEMBERDAYAAN EKONONMI LOKAL MELALUI PELESTARIAN HUTAN RAKYAT (Studi Kasus Hutan Rakyat Desa Regunung Kabupaten Semarang) - Darwanto, Darwanto (JURNAL PENELITIAN EKONOMI DAN BISNIS, 2011)
Regunung  village is one of village in Semarang regency that poses hutan rakyat (a forest that belong to society or people around the forest environment). Hutan rakyat is a result of sengonisasi program on society land. Society will  replace the land function and change the plant because sengon plant has high economic value.  Result of this study shows that Sengonisasi program of  hutan rakyat in  Regunung can increase welfare and decrease erosion degrees. Although in another village this program has not succeed already caused of nature condition that is not appropriate for sengon plant.Keyword: hutan rakyat  economy empowerment, sengon.